Towards semantically enriched e-learning assessment - Romero, Lucila; Gutiérrez, María de los Milagros; Caliusco, María Laura (My University, 2014)
The aim of this paper is to present the progress done in the development of an ontology network, named AONet that conceptualizes the e-assessment domain and supports the semi-automatic generation of assessment. Particularly, this paper is focused on ontology-based description of assessment as an educational resource, including the mappings between metadata standard specifications. The hypothesis of this work is that a proper description of assessment resources improves its location and retrieval by educators, learners and software systems and favors reuse and collaborative work.
Keywords: E-assessment; Ontology network; Ontology matching